Biological Study of the Oil Palm Pollinating Weevil (Elaeidobius kamerunicus) in Highland and Lowland Areas - Silfana,; Ginting, Makhrani Sari (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the biology of Elaeidobius kamerunicus in lowland and highland environments. The study was conducted at the Laboratory of the Indonesian Oil Palm Institute of Technology, Medan, from March to May 2026. Samples were collected from the Practical Plantation of the Indonesian Oil Palm Institute of Technology, located at an elevation of 14.46 m above sea level and representing the lowland site, and from PTPN IV Bah Birong Ulu Plantation, located at an elevation of 700 m above sea level and representing the highland site. Observations covered all developmental stages, including eggs, larvae, pupae, and adults. The results showed that E. kamerunicus developed more rapidly in the lowland environment than in the highland environment, as indicated by differences in the duration of the pre-adult stages and adult longevity between the two locations. These differences were presumed to be associated with variations in environmental temperature, which may influence insect metabolic rates and development. The findings provide scientific information that may serve as a basis for the management of E. kamerunicus populations to enhance pollination effectiveness and oil palm productivity under different environmental conditions.